Christian theology and African traditions - Michael, Matthew (Cambridge : The Lutterworth Press, 2013)
In this compelling work the evangelical theologian Matthew Michael sets out to reveal the unique nature of African Christianity and understand Christian theology in the context of the African worldview and traditions which have given African Christianity its unique religious stamp. Michael addresses the crucial obligation of Christianity to engage with African culture as a prerequisite to transforming African theology. He points out that a major flaw of Western missionary Christianisation was its failure to engage with African traditions, as a meaningful and vigorous Christianity cannot flouris.
The African Understanding of SalvationThe Biblical Understanding of Salvation; Important Aspects in Biblical Conception of Salvation; Conclusion; 10. The Holy Spirit; Introduction; The 'Benevolent' Spirits in Traditional African society; The Holy Spirit in Biblical Revelation; The Spiritual Gifts; Conclusion; 11. The Church; Introduction; Biblical Teachings on the Church; Conclusion; 12. The Future Hope; Introduction; Traditional African Eschatologcal Expectations; The Second Coming; The Millennium Reign; The Resurrection; The Final Judgment; Conclusion; 13. Conclusion; Bibliography.
Includes bibliographical references.
Online resource; title from PDF title page (ebrary, viewed November 29, 2013).
Master record variable field(s) change: 072
Keywords: Christianity -- Africa; Theology; RELIGION -- Christian Theology -- Systematic; RELIGION -- Christianity -- General; Christianity; Theology; Africa; RELIGION / Christian Theology / General; Electronic books